Comparative study on gynaecological issues in adolescence among private and government school girls - A., Egna Mahalekshmi; C., Poornima (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2016)
Background: Gynaecological problems of adolescents occupy a special spectrum of gynaecological disorder of all ages. This is because of the transitional phase of the physical nature of the problems which are so unique, special and specific for the age group and also because of the associated physiological factors which are very important in the growth and psychological remodelling of someone in the transition between childhood and womanhood. The study conducted with the objective to assess the extent of awareness regarding adolescent changes and problems among school going adolescents and to compare the same between government and private school adolescent girls. Methods: We used a preformed questionnaire as our study material to assess the knowledge and attitude regarding nutritional requirement, BMI, obesity, puberty changes, menstrual hygiene and irregularities, anaemia, vaginal discharge, gynaecological tumours and HPV vaccine among the adolescent girls in both government and private schools and thereby, to compare the same between them. Results: Awareness regarding nutritional requirement (45%, 98%), BMI (66%, 15.5%), obesity related gynaecological problems (9%, 81%) and causes for anaemia (28%, 93%) were less in government school girls when compared private school girls. Awareness on menstrual hygiene was satisfactory in both the groups. Awareness on HPV vaccination was unsatisfactory in both the groups. Conclusions: Government school girls need better health education regarding adolescent related gynaecological issues. There is need to educate both the groups on HPV vaccination.